Use of Synthetic Derivatives To Determine the Minimal Active Structure of Cytokine-Inducing Lipoteichoic Acid - Deininger, Susanne (American Society for Microbiology (ASM), 2007)
Lipoteichoic acid (LTA) from gram-positive bacteria is the counterpart to lipopolysaccharide from gram-negative bacteria. LTA, which activates Toll-like receptor 2 (TLR2), induces a unique cytokine and chemokine pattern. The chemical synthesis of LTA proved its immunostimulatory properties. To determine the minimal active structure of LTA, we reduced synthetic LTA in a number of steps down to the synthetic anchor and employed these molecules to stimulate interleukin-8 (IL-8) release in human whole blood. Ten times more of the synthetic structures with four to six d-alanine-substituted polyglycerophosphate units (50 nM) than of the native LTA preparation was required to induce IL-8 release. A further reduction to three backbone units with two or no d-alanine residues resulted in cytokine induction only from 500 nM. The synthetic anchor was not able to induce IL-8 release even at 5 μM. When the LTA derivatives were used at 500 nM, they induced increasing levels of IL-8 and tumor necrosis factor alpha with increasing elongation of the backbone. Peritoneal macrophages were less responsive than human blood to the synthetic structures. Therefore, TLR2 dependency could be shown only with cells from TLR2-deficient mice for the two largest synthetic structures. This was confirmed by using TLR2-transfected HEK 293 cells. Taken together, these data indicate that although the synthetic anchor (which, unlike the native anchor, contains only myristic acid) cannot induce cytokine release, the addition of three backbone units, even without d-alanine substituents, confers this ability. Lengthening of the chain with d-alanine-substituted backbone units results in increased cytokine-inducing potency and a more sensitive response.